Development of the eduka gantari website to improve literacy and numeracy in realizing the Profil Pelajar Pancasila - Robawati Robawati; Alifta Nurillah Kosasih; Riki Andriatna; Falach Noor Syahid; Sugiyani Sugiyani (JINOP (Jurnal Inovasi Pembelajaran))
Literacy and numeracy as a manifestation of critical reasoning in the Profil Pelajar Pancasila an important role in life, including in elementary school students. However, the achievement of literacy and numeracy skills of students is still relatively low. The aim of this research is to develop digital learning media with the "Eduka Gantari" website. This type of research is development research using the Plomp model which consists of three stages, namely the preliminary stage, the prototyping stage, and assessment phase. The results obtained from this research are in the form of digital learning media in the form of the "Eduka Gantari" website on the topic of Literacy and Numeracy which is valid, practical and effective. Data from the results of the research carried out showed that the average validation result was 4.21 on a scale of 5, the practicality of the media was up to 100% and the effectiveness in terms of the completeness aspect of learning outcomes from the pretest percentage was 48% and the posttest was 100%. Furthermore, the effectiveness of this media is from the average N-gain test for each ability, which is 0.72 for literacy skills and 0.74 for numeracy skills so that the product is in the high effective category. Thus, the media developed can provide opportunity for elementary school students to learn about Literacy and Numeracy because its valid, practical and effective in realizing the Profil Pelajar Pancasila.